Extração de cromenos a partir de Ageratum conyzoides L. : identificação química e modelagem matemática do processo - Almeida, Patrícia Carvalho (2015)
Extracts obtained from natural products have attracted the interest of pharmacological sector due to the chemical and biological properties. Therefore, in this work were studied the chromenes (precocene I and II) extraction processes, steam distillation and supercritical fluid extraction (SFE), from Ageratum conyzoides L. Essential oil was extracted by saturated steam at 1.0, 1.5, and 2.0 bar and the supercritical fluid extractions were performed at 40ºC and 90, 120, 150, and 200 bar to obtain non-volatile extracts. The essential oils were analyzed by gas chromatography/mass spectroscopy while the non-volatile extracts composition was determined by high-performance liquid chromatography. The essential oil presented two major compounds, precocene I (28.24  2.64%) and precocene II (28.55  2.08%). At 90 bar, the SFE resulted in higher yield and selectivity for precocene I and II, which represent 65.06% of extract. It was observed that the yield of chromenes varies according to pressure of SFE, however this behavior was not observed in the extracts obtained by steam distillation. A mathematical model was also used to simulate the processes and a good correlation was attained with the experimental data.